Oseltamivir Treatment for Influenza During the Flu Season of 2018–2019: A Longitudinal Study - Li, Xiao-Guang; Chen, Jing; Wang, Wei; Lin, Fei; Li, Lu; Liang, Jing-Jin; Deng, Zhong-Hua; Zhang, Bi-Ying; Jia, Ying; Su, Yuan-Bo; Kang, Yong-Feng; Du, Juan; et al. (Frontiers in Microbiology, 2022)
Background Oseltamivir resistance in influenza virus has been widely concerned. The increase of the frequency of viruses with reduced inhibition was observed. Whether the oseltamivir is effective is uncertain. We conducted a retrospective cohort study to understand the real-world situation in northern China and the clinical efficacy of patients with seasonal influenza after the use of oseltamivir. Methods The retrospective cohort study was performed on influenza-like cases in a tertiary general hospital in Beijing, China during the flu season of 2018-2019. All the influenza-like illness (ILI) cases (≥18 years) were recruited in the study. We analyzed the effect of the oseltamivir therapy on the number of clinic visit hospitalization and duration of fever and cough. Results A total of 689 ILI patients, who were meeting inclusion and exclusion criteria, were recruited in this retrospective cohort study. There were no significant differences on these characteristics between the oseltamivir and supportive therapy groups in the ILI patients or in the influenza virus positive patients. After adjusted for the potential confounders, oseltamivir therapy reduced the times of clinic visits in the ILI and influenza virus positive patients (P=0.036 and P=0.009). It was no effective with oseltamivir therapy on the outcome of hospitalization, and duration of fever and cough. Conclusions We did not observe the differences on the duration of fever, cough and the frequency of hospitalization between oseltamivir therapy and supportive therapy.